Endotracheal intubation in elective cervical surgery: A randomized, controlled, assessor-blinded study. Issue 43 (October 2017) - Fan, Hongna; Cao, Huijuan; Sun, Yingjie; Chen, Keyan; Diao, Yugang; Zhou, Nan; Yao, Guoquan; Zhou, Jin; Zhang, Tiezheng
Abstract: Background: We compared the effectiveness and safety of endotracheal intubation using the GlideScope (GS) video laryngoscope, CTrach laryngeal mask airway (LMA), or Shikani optical stylet rigid laryngoscope (SOS) during elective cervical surgery. Methods: Forty-five patients undergoing elective cervical surgery were randomly and equally assigned to endotracheal intubation via GS, LMA, or SOS airway management. Results: Endotracheal intubation was successfully completed in all patients. The mean intubation times of the groups differed significantly ( P < .01): GS, 17.9 ± 3.1 s; SOS, 40.4 ± 13.7 s; and LMA, 80.5 ± 22.5 s. The groups had similar heart rates and mean arterial pressures throughout the intubation, except that at 2 minutes after intubation the mean arterial pressure of the GS group (106.1 ± 18.5 mm Hg) was significantly higher than that of the LMA (89.7 ± 18.5 mm Hg) or SOS (89.7 ± 18.5 mm Hg; P < .01). The change in C2–5 Cobb angle from baseline was significantly higher in the GS group (GS, 34.2° ± 7.3°) than the LMA (24.4° ± 5.8°) or SOS (25.5° ± 6.4°); P < .01). Conclusions: The CTrach LMA and SOS rigid laryngoscope are effective, safe alternatives to the GS video laryngoscope for patients undergoing elective cervical surgery. Abstract : Supplemental Digital Content is available in the text